Pendekatan Menyenangkan untuk Meningkatkan Aktivitas dan Hasil Belajar IPS pada Siswa Kelas IX SMPN 1 Baradatu, Way Kanan TP 2022/2023 - Rahayu, Sri (STKIP PGRI Bandar Lampung, 2023)
The aim of the research is to describe the increased activity and social studies learning outcomes using a fun approach to Class IX students Junior High School of Baradatu 1, Way Kanan Regency, 2022/2023 Academic Year. The research method uses Classroom Action Research (CAR) through 4 stages of research namely planning, implementation, observation and reflection. Activities for 3 cycles. The research subjects totaled 30 students. The research instruments used observation sheets of learning activities and test sheets. Data analysis uses simple percentages. The results of the study showed an increase in social studies activities and learning outcomes in class IX students of Junior High School of Baradatu 1 in the 2022/2023 academic year.